Intercultural Dialogue in the European Education Policies A Conceptual Approach - Lähdesmäki, Tuuli; Koistinen, Aino-Kaisa; Ylönen, Susanne C. (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
XIV, 114 p. 1 illus.